Zika Virus and the Rio Olympic Games. Issue 6 (November 2019) - Hamilton, Bruce; Exeter, Dan; Beable, Sarah; Coleman, Lynne; Milne, Chris
Abstract : Objective: To evaluate the impact of Zika virus on preparation and management of the New Zealand (NZ) Olympic team. Design: Descriptive manuscript. Setting: New Zealand Olympic Health team preparation and management during the Rio de Janeiro Olympic Games, 2016. Patients (or Participants): New Zealand Olympic Team members. Interventions (or Assessment of Risk Factors): This manuscript describes the approaches used by the NZ Olympic Health team to the minimization of risk from Zika virus. Main Outcome Measures: Although descriptive of approach forms most of the article, the results of Zika virus serology are presented. Results: The NZ Olympic Health team took a proactive approach to risk mitigation, including extensive education, clothing changes, mosquito spray, mosquito nets, and voluntary postexposure testing. No positive serology was observed in those tested. Conclusions: The outbreak of Zika virus in Brazil, the associated complication of microcephaly, and the evolving understanding of virus transmission created significant uncertainty for NZ Olympic team members. The proactive approach taken by the health team to the mitigation of risk, combined with the anticipated low risk of arbovirus transmission over the period of the games, resulted in enhanced confidence from team members and no reports of positive serology.